Furious hours [compact disc, unabridged] : murder, fraud, and the last trial of Harper Lee - Cep, Casey N. (Books on Tape, 2019)
"The stunning story of an Alabama serial killer and the true-crime book that Harper Lee worked on obsessively in the years after 'To Kill a Mockingbird.' Reverend Willie Maxwell was a rural preacher accused of murdering five of his family members for insurance money in the 1970s. With the help of a savvy lawyer, he escaped justice for years until a relative shot him dead at the funeral of his last victim. Despite hundreds of witnesses, Maxwell's murderer was acquitted--thanks to the same attorney who had previously defended the Reverend. Sitting in the audience during the vigilante's trial was Harper Lee, who had traveled from New York City to her native Alabama with the idea of writing her own 'In Cold Blood,' the true-crime classic she had helped her friend Truman Capote research seventeen years earlier. Lee spent a year in town reporting, and many more years working on her own version of the case. Now Casey Cep brings this story to life, from the shocking murders to the courtroom drama to the racial politics of the Deep South. At the same time, she offers a deeply moving portrait of one of the country's most beloved writers and her struggle with fame, success, and the mystery of artistic creativity."--